Peningkatan Hasil Belajar Siswa Kelas V SD Negeri 1 Sumbersari Menggunakan Model Pembelajaran Probing Promting Tahun Ajaran Gasal 2021/2022 - Paini Paini (Perkumpulan Kualitama Edukatika Indonesia, 2022)
The aim of this research is to improve the learning outcomes of fifth grade students at SD Negeri 1 Sumbersari, Ngampel District, Kendal Regency using the Probing Prompting Learning Model for the 2021/2022 Odd School Year in the Mathematics subject of fractions. This research is classroom action research (PTK) with practice in cycle I and cycle II. The data collection techniques in this research are written test techniques, documentation, observation through cycle I and cycle II. Data analysis in this research is student learning outcomes in cycle I and student learning outcomes in cycle II using descriptive statistical tests. Students are said to obtain maximum results if the student's test score is more than the KKM, namely 75. The success indicator used is successful if it increases by more than or equal to 85% of the total number of fifth grade elementary school students who reach the KKM, namely 75. The results of this research are an increase Student learning outcomes from cycle I with a classical completeness percentage of 57.57% to cycle II and achieving classical learning completeness in cycle II reached 87.87%.